Investigating cultural uniqueness in theme parks through finding relationships between visual integration of visitor traffics and capacity of service facilities. (September 2016) - Hoon Hyun, Kyung; Min, Aram; Kim, Sun-Joong; Lee, Ji-Hyun
The goal of the article is to find the relationships between theme park visitor traffics and service facility location along with their capacities. To do that, we analyzed four Disneylands situated in Paris, Tokyo, and the United States (Florida and California). By analyzing the visual integration of visitor traffics at each Disneyland and calculating the capacities of service facilities such as the attractions, shops, and restaurants, we ran through a linear and a geographically weighted regression analysis. Our results indicate that there is a unique relationship between the service facility placements and the amount of predicted traffic flows for each Disneyland.